(untitled) (Bangladesh Journal of Botany, 2019)
The role of L-lysine (Lys) on some cytogenetic and physiological parameters in Allium cepa L. seeds exposed to salt was evaluated. NaCl stress on the other hand showed a significantly inhibitory effect on the seedling growth and seed germination of Allium cepa. Besides, it significantly reduced the mitotic index in the root tip meristems of seeds and increased micronuclei which are the most effective and simplest indicator of cytological damage and chromosomal abnormalities. However, the effects of salinity on chromosomal aberrations, seedling growth, seed germination and mitotic activity have decreased significantly with Lys application.